Hungarian Monitoring, 22 December 1988 . [Magyar rádiófigyelő], 1988. december 22 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Pan Am plane crashes over Scotland - Changes in the Polish Party leadership - On the problems of Armenian refugees - Newspaper article on Belarusian tragedy in the 1930s - Disarmament press conference in Moscow - Shevardnadze in the People's Republic of Korea - Romanian-Yugoslav summit Domestic Affairs: - Parliamentary coverage - Danube movements initiate campaign against evangelical bishop Gyula Nagy who voted for construction of Gabčíkovo-Nagymaros dam - Károly Grósz announces that the Party supports Young Communist League (KISZ) new initiatives - Interview with Mátyás Szűrös who conveyed Pope John Paul II's message to representatives in Parliament Economy: - A. Springer joint West German-Hungarian company formed in Budapest Külpolitika: - Skócia fölött lezuhant PANAM - Változások a lengyel pártvezetésben - Az Örményországból áttelepülők problémáiról - Újságcikk a belorussziai 30-s években történt tragédiáról - Leszerelési sajtótájékoztató Moszkvában - Sevardnadze Népi Koreában - Román-jugoszláv csúcstalálkozó Belpolitika: - Országgyűlési tudósítások - A Duna mozgalmak kampányt indítottak Nagy Gyula evangélikus püspök, képviselő ellen, mert a Bős-Nagymarosi erőmű megépítése mellett szavazott - Grósz Károly közölte, hogy a párt támogatja a KISZ újszerű kezdeményezéseit - Interjú Szűrös Mátyással,aki a Parlamentben tájékoztatta a képviselőket II. János Pál pápa üzenetéről Gazdaság: - Megalakult az Axel Springer Budapest magyar-nyugatnémet vegyesvállalat